A szabadság bolond körei - Dér, András; Muhi, Klára (Hungary : M&M Film Company, 2018)
The “madhouse” of Intapuszta was located far from the capital, in the remote Batthyány castle. It was a legendary institution in the 1960s and 1970s, where tolerated artists and anti-state aristocrats lived together with ordinary patients. Intapuszta was the first humane, fenceless, work-therapy institution in Hungary. It blossomed in the 1960s when Dénes Goldschmidt became the director of the institute. The reform psychiatrist created a special shelter—an antipsychotic institution for people who could not adapt to the "normal world". In this particular subculture, both the patient and the caregiver thrived. They held theater performances, organized their own radio show, edited literary anthologies, and organized sport competitions (the “Crazy Olympians”).
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films